ETHNOCONSTRUCTIVISM E-MODULE TO IMPROVE PERCEPTION, INTEREST, AND MOTIVATION OF STUDENTS IN CLASS V ELEMENTARY SCHOOL - Asrial, Asrial; Syahrial, Syahrial; Maison, Maison; Kurniawan, Dwi Agus; Piyana, Suci Okta (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
This study aims to develop instructional media in the form of teaching materials in the form of electronic modules by using the Pageflip Professional 3D software application for fifth grade elementary school students. The method in this study uses the Research and Development (R & D) method that adapts the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Based on the results of the assessment in this study on the questionnaire obtained the frequency perception of 28 students with a percentage of 93.4% in the sufficient category. For the interest questionnaire to get frequency as many as 24 students with a percentage of 80.1% in the good category. While the motivation questionnaire obtained frequency of 28 students with a percentage of 93.4% in the good category. The resulting data shows that the electronic ethnocontructivism module based on the Pageflip Professional 3D software developed can be used as teaching material in the learning process.